E-Vitamin Infused Highly Cross-Linked Polyethylene: RSA Results from a Randomised Controlled Trial Using 32 mm and 36 mm Ceramic Heads. Issue 1 (January 2015) - Lindalen, Einar; Nordsletten, Lars; Høvik, Øystein; Röhrl, Stephan M
Background: Polyethylene wear has been a major cause of revision of cementless total hip replacements. Highly cross-linked polyethylene has been developed to increase mechanical resistance to wear. However, cross-linking from irradiation of the polyethylene generates free radicals and these can oxidise in vivo and might over time alter the initial mechanical properties. Vitamin-E infused highly cross-linked polyethylene has been developed to reduce the amount of free radicals without compromising the mechanical properties. Purpose: To measure wear of vitamin E infused highly cross-linked polyethylene and compare wear between 2 different head sizes. Methods: In a prospective randomised study between 32 mm and 36 mm Biolox ® delta heads in 50 hips we analysed the in vivo wear of the E-poly ™ with markerless radiostereometry. Results: Mean (95% CI) wear for the total material was 0.041 mm (0.015-0.066) in the vertical direction and 0.177 mm (0.155-0.200) in the total 3D direction. After the anticipated period of bedding-in we found no statistically significant differences in wear from three months to 2 years in vertical and total 3D directions. Although statistical significant differences between 32 mm and 36 mm heads were found in the total 3D direction we cannot conclude that there are significant clinical important differences in wear comparing these head sizes. Conclusions: This study shows promising early results with very low wear, even for 36 mm heads, but long term follow-up is necessary to evaluate if this polyethylene will provide low wear and good mechanical properties in the long-term.